A case of Osler-Weber-Rendu syndrome, diagnosed at geriatric age, presenting with gastrointestinal bleeding, telangiectasias, and asymptomatic liver and lung angiodysplasia - ŞH Aktaş; S. Basat (Egyptian Liver Journal, 2024)
Abstract Background Osler-Weber-Rendu syndrome (OWRS) is an autosomal dominant disease with recurrent epistaxis, mucocutaneous telangiectasias, and arteriovenous malformations. Its clinical presentation ranges from simple skin lesions to life-threatening complications. When the diagnosis of the disease is delayed, it can be mortal and have high morbidity. This case is presented because OWRS is rare, and although she has all the features of the disease, she was diagnosed in the geriatric age group. Case presentation A 72-year-old female patient who applied to the emergency department with the complaint of melena was diagnosed with upper gastrointestinal system bleeding. Gastroscopy revealed angiodysplasia in the bulb. Colonoscopy was normal. She had telangiectasias on her face, maxilla, nose, tongue and lips. She also had recurrent epistaxis and a family history. Thorax CT showed aneurysmatic vascular malformations in the lung. Abdominal MRI revealed vascular malformations in the liver. Brain MRI was normal. The patient was diagnosed with OWRS according to the Curaçao diagnostic criteria because of telangiectasia in the mouth, nose, and face, angiodysplasia in the gastric bulb, aneurysmatic vascular dilatation in the lung, vascular pathologies in the liver, and a history of epistaxis and telangiectasia in the patient’s family members. Conclusion This patient is presented because OWRS is rare, and although she has all the features of the disease, she was diagnosed in the geriatric age group. Clinicians should be aware of this rare disease. Especially in the elderly, when angiodysplasia causing gastrointestinal bleeding is detected, it should be considered in the differential diagnosis that this may be an OWSR case.